Exploring the Implementation of Religious Character Values in Islamic and Moral Education at Primary Schools - Karmilah, Karmilah; Fakhri, Jamal; Anwar, Chairul (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2025)
Religious character education was a fundamental aspect in shaping a generation that was not only intellectually intelligent but also morally upright. Amid increasingly complex moral challenges, instilling religious values from the elementary school level had become a critical need. This study aimed to analyze the implementation of religious character values in Islamic Religious Education and Character Education subjects at elementary schools in Menggala District, Tulang Bawang Regency. It also sought to identify the forms of religious character developed in students and the supporting and inhibiting factors in the value formation process. Using a qualitative approach with a phenomenological method, data were collected through interviews, observations, and documentation at three purposively selected elementary schools. The results showed that teachers played a central role through strategies such as the habituation of 6S, religious role modeling, and integration of Islamic values in lessons. The dominant religious values instilled included faith in Allah, discipline, responsibility, tolerance, honesty, and compassion. The main supporting factors were school support, parental involvement, and a religious social environment. In contrast, the main inhibiting factors included limited instructional time, inadequate facilities, and inconsistency in religious practices at home. These findings highlighted the importance of synergy between schools, families, and communities in sustainably fostering students' religious character.